Speech and silence in monastic models of holiness: Gaul/Francia, 400-750 - Chaloner, JD (2020)
Scholars often assume a break between Late Antiquity and the Medieval Era, but there is more continuity there than is always recognised. The great changes which come about in the medieval period make the continuity of ideas even more surprising. One place in which we witness this is in the endurance of late-antique views concerning the spiritual life as a journey toward perfection. This view was picked up on by Merovingian monastic writers, thereby allowing authors to guide and direct their monastic readers towards perfection. In order to demonstrate this, this thesis considers the role speech and silence played in four case studies, and how authors were able to adapt late-antique ideas to their own contexts. I order my study as follows: Chapter 1 begins by looking at rhetoric in the Late Roman Empire, concentrating particularly on frank speech in ascetic movements; Chapter 2 analyses John Cassian’s writings as an example of how he applied these ideas in his late-antique Gallic context, with particular attention to how he used sleep and silence to both reveal and create holiness in his readers; Chapter 3 examines the writings of Caesarius of Arles and his followers, demonstrating the adaptation of late-antique ideas for the female monastics of St. John’s and Radegund’s Holy Cross; Chapter 4 evaluates the writings of Columbanus and his followers, analysing how the same ideas were used to display the holiness of his male and female disciples in different contexts; Chapter 5 discusses the little-studied florilegium the Liber scintillarum, its purpose and the way in which it used late-antique ideas to establish holiness in a wider group of people. These cases studies demonstrate the continuity of late-antique ideas throughout the Merovingian period.